The Landscape and Implications of Chimeric RNAs in Cervical Cancer - Wu, Peng (EBioMedicine, 2018)
BACKGROUND: Gene fusions and fusion products have been proven to be ideal biomarkers and drug targets for cancer. Even though a comprehensive study of cervical cancer has been conducted as part of the Cancer Genome Atlas (TCGA) project, few recurrent gene fusions have been found, and none above 3% of frequency. METHODS: We believe that chimeric fusion RNAs generated by intergenic splicing represent a new repertoire of biomarkers and/or therapeutic targets. However, they would be missed when only genome sequences and fusions at DNA level are considered. We performed extensive data mining for chimeric RNAs using both our and TCGA cervical cancer RNA-Seq datasets. Multiple criteria were applied. We analyzed the landscape of chimeric RNAs at various levels, and from different angles. FINDINGS: The chimeric RNA landscape changed as different filters were applied. 15 highly frequent (>10%) chimeric RNAs were identified. LHX6-NDUFA8 was detected exclusively in cervical cancer tissues and Pap smears, but not in normal controls. Mechanistically, it is not due to interstitial deletion, but a product of cis-splicing between adjacent genes. Silencing of another recurrent chimera, SLC2A11-MIF, resulted in cell cycle arrest and reduced cellular proliferation. This effect is unique to the chimera, and not shared by the two parental genes. INTERPRETATION: Highly frequent chimeric RNAs are present in cervical cancers. They can be formed by intergenic splicing. Some have clear implications as potential biomarkers, or for shedding new light on the biology of the disease. FUND: Stand Up To Cancer and the National Science Foundation of China.